From Face-to-Face to Online Mode: Nursing Students’ Learning Experiences during COVID-19 Pandemic - Basnet, Pritika (Scholars’ Journal, 2021)
The repeated episodes of global pandemic created by COVID-19 has lead several universities and institutes switching their mode of education from traditional face-to-face to online mode using different platforms such as Zoom, Google Meet, etc. to mitigate the impact on learning. Nursing education system has been affected such as student’s learning, gap in admissions and delay in graduation which could in turn lead to nursing shortage in near future. The consequences, challenges and barriers faced by students must be explored and addressed so as to improve the quality of online system of nursing education in order to yield smooth production of nursing graduates. This narrative inquiry explores the stories of two nursing student’ experiences who were adapting online mode of education during COVID-19 pandemic. The findings of the study explored as feeling of uncertainty, COVID-19 prompted new learning, modes of teaching and learning and barriers to online learning such as technological competencies, lack of interaction, the Internet issues. The study highlighted that there is a need of social interactions between students and teachers and among students for an active learning process. In addition, practical courses remain the major concern in nursing and it can lead to anxiety and delay graduation among nursing students. So, concerned authority must be alerted for adopting alternative mode of clinical education as well.